Pengembangan Toleransi Beragama Siswa Melalui Aktivitas Pembelajaran di Kelas Dengan Metode Komunikatif - Fanani, Adip; Aziz, Rahmat (Jurnal Penelitian, 2023)
Education has an important role in developing the value of  religious tolerance in students. Learning in the classroom has a strategic role in developing it. This research aims to determine the influence of  the learning process in the classroom on students’ religious tolerance. The research subjects were 210 students who were randomly selected from two junior high schools in the city of  Malang, East Java. Data was collected through a class activity scale and a religious tolerance scale. Analysis was carried out using simple regression techniques. The results of  the analysis of  the influence of  class activities on students’ religious tolerance character, there are six classroom activity indicator factors, namely: classroom rules, student support, student involvement, positive learning, teacher support, class management. Of  these six indicators, the most influence on students’ religious tolerance character. is the rule in the class with the regression results getting a significance value (0.13<0.05). The results of  this research have the implication that classroom rules can influence students’ religious tolerance by 59%.